Recent Advances in Synthesis, Characterization and Applications of Innovative Materials in Removal of Water Contaminants - Dippong, Thomas (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue focuses on the application of innovative materials in water decontamination, the synthesis and characterization of engineered nanocomposites,water decontamination by photocatalysis, adsorption and other techniques, and computational and theoretical studies of the reaction mechanisms, kinetics and thermodynamics of water depollution processes. Engineered nanomaterials with magnetic properties allow the adsorption of contaminants, followed by magnetic separation, while other nanomaterials allow the contaminant's photodegradation. The use of these innovative materials, whether for pollutant adsorption or decomposition by photocatalysis, or for constructing low-cost sensors for the detection of contaminants, has gained interest in the preceding decades.